Experimental and numerical investigations of pin-ended hot-rolled stainless steel angle section columns failing by flexural buckling - Zhang, Lulu (2022)
A thorough testing and numerical modelling programme has been conducted to investigate the flexural buckling behaviour and strengths of pin-ended hot-rolled stainless steel angle section columns. The testing programme adopted three hot-rolled stainless steel equal-leg angle sections, and included 12 pin-ended column tests about the minor principal axis as well as supplementary initial geometric imperfection measurements on the column specimens. The testing programme was accompanied by a parallel numerical modelling programme, including a validation study, where finite element models were developed and validated against the test results, and a parametric study, where the validated finite element models were employed to generate additional numerical data over a broad spectrum of cross-section dimensions and member effective lengths. The test and numerical data were then adopted to evaluate the accuracy of the relevant design rules, as given in the European code and American design guide, for pin-ended hot-rolled stainless steel angle section columns prone to flexural buckling about the minor principal axis. On the basis of the evaluation results, it can be concluded that (i) the European code results in overall accurate and consistent flexural buckling strength predictions, but many of the predictions for short and intermediate columns with member non-dimensional slendernesses less than around 1.0 are unsafe, and (ii) the American design guide leads to unduly conservative and scattered flexural buckling strength predictions. Finally, a new design approach was developed through modifications to the Eurocode design rules, and shown to offer accurate, consistent and safe-sided flexural buckling strength predictions for pin-ended hot-rolled stainless steel angle section columns over the whole considered range of member non-dimensional slendernesses up to 4.0. The reliability of the new design approach was confirmed by means of statistical analyses according to EN 1990.